Fostering Children’s Critical Thinking Skills through Problem-Based Interactive Worksheets at Sekolah Rakyat Merdeka Kalimantan Tengah - Fitri, Nur Annisa; Shofiya, Nur Aini; Norliani, Norliani; Razzaq Kurniawan, Muhammad Abdul; Azahra, Nicha Chairunnisa; Nengsih, Dora; Aisyah, Aisyah; Haryanti, Ferina; Utami, Hana Putri; Anshari, Hafiz; Syahid, Abdul (Lembaga Dongan Dosen, 2025)
Critical thinking is an essential skill that must be stimulated from early childhood, particularly in non-formal learning environments that do not follow standardized instructional structures. Sekolah Rakyat Merdeka Kalimantan Tengah is an independent non-formal educational community with fluctuating participant numbers and a heterogeneous age range, necessitating flexible, engaging learning media that can be implemented within a single session. This activity aims to stimulate and foster children's critical thinking skills through problem-based interactive worksheets that promote problem identification, solution selection, and justification. The activity was conducted in one session using a descriptive–exploratory qualitative approach and employed two interactive worksheets, namely Problem and the Right Place and Problem and the Things to Use. Data were collected through direct observation, worksheet results, children's verbal responses, and scoring using a reasoning rubric on a scale of 0 to 3. The findings indicate that the problem-based interactive worksheets successfully stimulated children's basic critical thinking abilities, as reflected in the varying quality of reasoning among participants aged five to thirteen. Younger children tended to provide literal explanations, whereas older children demonstrated more logical and analytical reasoning. These findings suggest that problem-based interactive worksheets are practical, simple, and easily adaptable learning media for fostering children's critical thinking skills in non-formal educational contexts.